The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1932296813511734
|View full text |Cite
|
Sign up to set email alerts
|

Average Daily Risk Range (ADRR) in Young Children With Type 1 Diabetes

Abstract: Hemoglobin A1c (A1c) is widely regarded as the gold standard for evaluating glycemic control in youth with type 1 diabetes.1 However, A1c represents average glucose levels over the past 6-12 weeks and may not adequately represent the degree of blood glucose (BG) excursions experienced, particularly hypoglycemic episodes.2,3 Greater frequency of BG excursions, even excursions lasting brief periods of time, is related to increased risk for development of diabetesrelated complications. 4 Thus, standardized evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…1,13 In the current study, 56% of youths had ADRR scores in the high-risk category. This percentage was lower than the percentage of very young children with T1DM with ADRR scores in the high-risk category as reported by Monaghan et al 9 (73.1%) and Patton et al 10 (69%), but much higher than the percentage of adults with T1DM with ADRR scores in the high-risk category as reported by Kovatchev et al 8 (28%). Unlike the previous adult study, 8 when tested against a variety of other measures of GV, the ADRR scores in this sample of youths was not equally accurate in predicting the percentage of episodes of hyper-or hypoglycemia.…”
Section: Discussioncontrasting
confidence: 37%
See 4 more Smart Citations
“…1,13 In the current study, 56% of youths had ADRR scores in the high-risk category. This percentage was lower than the percentage of very young children with T1DM with ADRR scores in the high-risk category as reported by Monaghan et al 9 (73.1%) and Patton et al 10 (69%), but much higher than the percentage of adults with T1DM with ADRR scores in the high-risk category as reported by Kovatchev et al 8 (28%). Unlike the previous adult study, 8 when tested against a variety of other measures of GV, the ADRR scores in this sample of youths was not equally accurate in predicting the percentage of episodes of hyper-or hypoglycemia.…”
Section: Discussioncontrasting
confidence: 37%
“…This outcome is similar to the results of a previous cross-sectional study of ADRR scores in very young children with T1DM, which also found that scores did not correlate with the percentage of concurrent moderate hypoglycemic episodes. 9 Although our findings demonstrate that the ADRR does not predict future episodes of hypoglycemia, we did identify more accurate measures of future risk for hypoglycemia in youths, which were LBGI, the percentage of moderate hypoglycemic events in Month 1, and CoV. Likewise, we determined that the adult risk categories, when used in youths, appear limited to only predicting a youth's likelihood of future hyper-or euglycemia and not episodes of hypoglycemia.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations